Palaeoenvironmental conditions preceding the Messinian Salinity Crisis: A case study from Gavdos Island - Hara Drinia; Assimina Antonarakou; Nikolaos Tsaparas; George Kontakiotis (Geobios, 2007)
The Messinian pre-evaporitic sedimentary succession of Gavdos Island (Metochia section) is a nearly uninterrupted succession of marine sediments, dominated by finely laminated diatomaceous marls, which are cyclically alternating with clayey diatomites and white diatomites. The qualitative and quantitative analysis of the planktonic foraminiferal fauna allowed the recognition of nine bioevents, which have been astronomically dated for the Mediterranean. The base of the diatomitic succession in Gavdos Island is dated at 6.722Ma and the top at 6.015Ma. The studied section contains benthic foraminiferal genera characteristic of an outer shelf to slope environment. The qualitative and quantitative analysis of this microfauna revealed three benthic foraminiferal fossil assemblages and the occurrence of allochthonous species transported into the bathyal environment by current activity. The cyclical pattern of the benthic foraminifera assemblages indicates that the studied sediments have been affected by repeated episodes of basin restriction characterized by low diversity benthic foraminifera populations, and a limited planktonic foraminifer association typified by shallow, surface-dwelling forms. This restriction was partly due to Antarctic cooling, which produced palaeo-Mediterranean sea-level oscillations during the Early Messinian, as a prelude to closure of the Atlantic connections. The relative impact of climatic versus tectonic control on sedimentation patterns within this basin is discussed. Résumé Les sédiments marins du Messinien pré-évaporitique de l’île de Gavdos (coupe de Metochia) sont quasi continus et dominés par des marnes diatomitiques finement laminées alternant de façon cyclique avec des diatomites argileuses et des diatomites blanches. L’analyse qualitative et quantitative de la faune de foraminifères planctoniques a permis la mise en évidence de neuf événements biologiques qui ont été datés par l’astrochronologie à l’échelle de la Méditerranée. La base de la succession diatomitique de l’île de Gavdos date de 6,722Ma et son sommet de 6,015Ma. La coupe contient des genres de foraminifères benthiques caractéristiques d’un environnement allant de la plate-forme externe au talus. L’analyse qualitative et quantitative de cette microfaune révèle trois assemblages de foraminifères benthiques et la présence d’espèces allochtones apportées dans le domaine bathyal par l’activité des courants. Le caractère cyclique des assemblages de foraminifères benthiques indique que ces sédiments ont été affectés par des épisodes répétés de confinement du bassin caractérisés par la faible diversité des populations de foraminifères benthiques et une association restreinte de foraminifères planctoniques marquée par des formes affectionnant les habitats de surface dans des eaux de faible profondeur. Ce confinement était en partie dû au refroidissement antarctique qui entraîna des oscillations du niveau marin de la Méditerranée pendant le Messinien inférieur en prélude à la fermeture des corridors de connexion avec l’océan Atlantique. Les impacts relatifs des forçages du climat et de la tectonique sur les processus sédimentaires dans ce bassin sont discutés.
Keywords: Benthic foraminifera; Diatomaceous marls; Foraminifères benthiques; Gavdos; Marnes diatomitiques; Messinian; Messinien; Palaeoenvironment; Paléoenvironnement